Malapraktik Medis dalam Perspektif Hadits Riwayat Abu Dawud dan Pasal 58 UU No 36 tahun 2009: Studi Perbandingan - Savariah, Eva; Arifin, Tajul (Universitas Islam Negeri Alauddin Makassar, 2024)
Malpractice is basically a social phenomenon so that it attracts a lot of public attention, not only among doctors but also human rights activists. Because malpractice in the world of medicine affects humans, physical losses and victims' property. The legal system in Indonesia does not yet have definite provisions regarding this case, so judges tend to use ordinary procedural law as a guideline. The purpose of the author in writing this article is as follows: 1) To find out how the perspective of hadith on medical malpractice. 2) To find out how the application of criminal law in Indonesia against medical malpractice. The research method that the authors use in this article is a qualitative approach with descriptive analysis techniques. The results of the research show that the hadith HR. Abu Dawud has the same meaning, that is, doctors or medical personnel must be held responsible for the mistakes they have made, because of the patient's losses, both physically, spiritually and psychologically. The government regulates health in the Law of the Republic of Indonesia No. 36 of 2009 concerning Health which was previously Law No. 23 of 1992. So patients who suffer losses can report the doctor or medical personnel through the Doctors Association organization in Indonesia or the existing Medical Discipline Honorary Council. in Indonesia (MKDKI) or the Medical Ethics Honorary Council and can also go through the High Court if it is in the form of a crime by including evidence of being a victim of medical malpractice.